2023
DOI: 10.1007/s40618-023-02169-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mediterranean diet in endocrine diseases: a joint overview by the endocrinologist and the nutritionist

L. Barrea,
L. Verde,
G. Annunziata
et al.

Abstract: Purpose The purpose of this review is to examine the current evidence on the potential role of Mediterranean diet (MD) in the prevention and management of endocrine disorders and to highlight the importance of interdisciplinary collaboration between endocrinologists and nutritionists. Methods A literature search was conducted using PubMed and Google Scholar databases to identify relevant studies published in English. Studies were selected based on their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 180 publications
(237 reference statements)
0
7
0
Order By: Relevance
“…A comprehensive literature search emphasized the interdisciplinary collaboration between endocrinologists and nutritionists to obtain the best possible management of endocrinal diseases, such as the possible impact of the MD concerning their preventive and confronted approaches against these [ 26 ]. The above evidence suggested that the MD could exert a preventing impact on endocrinal diseases as well as its introduction into nutritional proposals, which could be proved favorable [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive literature search emphasized the interdisciplinary collaboration between endocrinologists and nutritionists to obtain the best possible management of endocrinal diseases, such as the possible impact of the MD concerning their preventive and confronted approaches against these [ 26 ]. The above evidence suggested that the MD could exert a preventing impact on endocrinal diseases as well as its introduction into nutritional proposals, which could be proved favorable [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…MD, celebrated for its emphasis on whole, nutrient-dense foods, has emerged as a dietary pattern of concern in lowering the probability of diabesity. The study by InterAct Consortium (2011) investigated the link of MD compliance with the risk of insulin-independent diabetes [ 26 , 27 , 28 ]. This extensive European study found a notable association: individuals who adhered closely to the MD experienced a reduced probability of insulin-independent diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…It can change the hypothalamic-pituitarythyroid (HPT) axis, which controls how much (TSH) is released from the pituitary gland and how it is affected by feedback. Arsenic exposure may change the production and sensitivity of (TSH), which can throw off the balance of thyroid hormones as a whole [74]. Salvia hispanica seeds powder possess a substantial quantity of antioxidants, comprising polyphenols and omega-3 fatty acids.…”
Section: Effects Of Salvia Hispanica Seeds Powder On Thyroid Hormone ...mentioning
confidence: 99%
“…The Mediterranean diet (MD) constitutes one of the most well-recognized dietary patterns, which has been increasingly found to exert diverse beneficial effects on human health, promoting a great daily quality of life and healthy aging, as well as increasing life expectancy [ 1 , 2 ]. The MD has been considered a beneficial dietary pattern by decreasing the risks of a variety of human disorders and pathological states, including metabolic disorders [ 3 , 4 , 5 ]. The MD, initially invented by Ancel Keys [ 6 ] in 1960, is a plant-based diet comprising high amounts of vegetables, fruits, legumes, wholegrain cereals, nuts and extra virgin olive oil, the moderate consumption of dairy products, seafoods and poultry, and the low intake of saturated fats and processed red meat products [ 7 ].…”
Section: Introductionmentioning
confidence: 99%